Clinical and pathological characteristics of 7 cases of colorectal cancer in organ transplant recipients - Wang Ye; Lou Zheng; Meng Ronggui; Ji Liqiang; Li Shuyuan; Zheng Kuo; Jin Lu; Gong Haifeng; Liu Lianjie; Hao Liqiang; Zhang Wei (结直肠肛门外科)
[Objectives] To analyze the clinical and pathological characteristics of colorectal cancer in organ transplant recipients and provide references for clinical diagnosis and treatment. [Methods] Retrospective analysis of 7 organ transplant recipients confirmed with colorectal adenocarcinoma who underwent radical surgery at the Department of Colorectal Surgery of the First Affiliated Hospital of Naval Medical University from September 2002 to September 2021 was performed. Clinical and pathological characteristics of colorectal cancer in organ transplant recipients were summarized and analyzed. [Results] The initial symptoms were hematochezia in 3 cases, abdominal pain in 1 case, diarrhea in 1 case, abdominal distension and vomiting in 1 case, and abnormal colonoscopy in 1 case. The preoperative serum levels of CEA were 1.61 to 123.20 ng/mL, the median serum CEA level was 5.12 (1.76, 10.28) ng/mL; the preoperative serum levels of CA199 were 4.79 to 184.96 U/mL, and the median serum CA199 level was 18.59 (9.37, 135.60) U/mL. Three patients had normal preoperative serum CEA, and five had normal preoperative serum CA199. The tumor was located in the ascending colon in 1 case, descending colon in 1 case, sigmoid colon in 1 case, rectosigmoid junction in 1 case, and rectum in 3 cases. Among them, 3 cases at stage Ⅲ, 3 cases at stage Ⅱ, and 1 case at stageⅠ;3 cases were poorly differentiated, 1 case was moderately to poorly differentiated, and 3 cases were moderately differentiated; The tumor occupied less than the entire intestinal circumference in 2 cases and the entire intestinal circumference in 5 cases. [Conclusion] Colorectal cancer in organ transplant recipients tends to occur within five years, and the tumor is usually located in the rectum, with most patients diagnosed with locally advanced stage. Therefore, for individuals who have undergone organ transplantation, it is recommended to strengthen early diagnosis and treatment of colorectal cancer to improve prognosis.